Determinación de los factores socio económicos para el micro emprendimiento de los productores de naranja en la comuna Charquiyacu, del cantón Caluma de la provincia de Bolívar - Muñoz Franco, Angélica Alejandra (2016)
The study analyzed the orange production sector in the Canton Caluma, with direct approaches to each of the producers, and investigating important bibliography to strengthen and deepen the knowledge about this activity, and in this way to be able to formulate the conclusions and recommendations That direct the optimization of the processes of those who start the orange production chain, who are currently the least benefited. The development of the work was initiated by identifying and approaching the problem, which arises from the decadent social and economic situation of the inhabitants of the Charquiyacu Commune, which is born of a poor process in the production and marketing of orange that does not allow To improve the living conditions of the inhabitants of the Commune……..